Hard-Soft Core-Shell Architecture Formation from Cubic Cobalt Ferrite Nanoparticles - Sanna Angotzi, Marco; Mameli, Valentina; Zákutná, Dominika; Secci, Fausto; Xin, Huolin L; Cannas, Carla (Nanomaterials (Basel, Switzerland), 2023)
Cubic bi-magnetic hard-soft core-shell nanoarchitectures were prepared starting from cobalt ferrite nanoparticles, prevalently with cubic shape, as seeds to grow a manganese ferrite shell. The combined use of direct (nanoscale chemical mapping via STEM-EDX) and indirect (DC magnetometry) tools was adopted to verify the formation of the heterostructures at the nanoscale and bulk level, respectively. The results showed the obtainment of core-shell NPs (CoFe2O4@MnFe2O4) with a thin shell (heterogenous nucleation). In addition, manganese ferrite was found to homogeneously nucleate to form a secondary nanoparticle population (homogenous nucleation). This study shed light on the competitive formation mechanism of homogenous and heterogenous nucleation, suggesting the existence of a critical size, beyond which, phase separation occurs and seeds are no longer available in the reaction medium for heterogenous nucleation. These findings may allow one to tailor the synthesis process in order to achieve better control of the materials' features affecting the magnetic behaviour, and consequently, the performances as heat mediators or components for data storage devices.
Keywords: STEM-EDX; heterostructures; cobalt ferrite; cubic shape; core–shell